Drivers of E-Business Diffusion in Tourism: A Decision Tree Approach - Rondović,Biljana (Universidad de Talca, 2019)
Abstract:The aim of this paper is to examine the individual and interactive influence of organizational, technical and environmental factors on the diffusion of e-business in Montenegrin tourism organizations. In accordance with this goal a decision tree method is used in this paper. The results showed that organizational factors have the highest individual impact on e-business diffusion and that there is a strong interactive influence of organizational, information technology integration and external support factors. The obtained results provide important information for management and decision-making in conditions when diffusion of information technology innovation needs to be accelerated in such a way that instead of influencing only one group of factors, it affects several factors simultaneously which, in interaction with one another, lead to a greater degree of e-business diffusion.